(3HQeLI HjSc eHSWI (B=s Basic programming made simple : (3YQV eHSW dHQeLI GdMGSH GdEdcJQhfj HdZI GdHjSc (B/s - (3gjKe GdhQOjs ((3GdbGgQI (B:s (3GdOGQ GdYQHjI ddYdhe,s, 1987)
(3GdeHGOF GdCSGSjI(B.s
Keywords: (3HjSc (B((3dZI HQeLI(B)s; (3GdHQeLI (B((3MGSHGJ EdcJQhfjI(B)s; (3GdMGSHGJ GdEdcJQhfjIs -- (3dZGJs